(untitled) (International Journal of Innovative Technologies in Economy, 2024)
Introduction. The management of liquidity and market risks in the banking sector is of paramount importance for maintaining a robust financial system and mitigating potential crises. Despite extensive research and implementation of risk management techniques, recent experiences have highlighted the inadequacy of purely statistics-based approaches in extreme situations. This study aims to critically examine the current state of banking risk management, focusing on the effectiveness of methods such as Value at Risk (VaR) for foreign currency risks and Gap Analysis for liquidity and interest rate risks. By identifying limitations and proposing enhancements, this research seeks to contribute to the development of more resilient risk management frameworks in the banking industry. Methods. This study employs a comprehensive literature review and empirical analysis of risk management practices in the banking sector. VaR and Gap Analysis methods are applied to real-world data from a representative sample of banks to assess their efficacy in capturing and mitigating liquidity, foreign currency, and interest rate risks. The results are critically evaluated using advanced statistical techniques and benchmarked against industry standards. Results. The findings reveal significant limitations in the current application of VaR and Gap Analysis methods, particularly in extreme market conditions. The study identifies key factors contributing to these shortcomings and proposes a set of enhanced risk management strategies that incorporate scenario analysis, stress testing, and machine learning techniques. These innovations demonstrate improved risk capture and mitigation capabilities. Discussion. The outcomes of this research have significant implications for risk management practices in the banking sector. The proposed enhancements to VaR and Gap Analysis methods offer a pathway towards more robust and adaptive risk frameworks. Future research should focus on the practical implementation and validation of these strategies across a wider range of banking institutions and market conditions.